Studying Fast Reaction Kinetics with Online NMR Spectroscopy1. Issue 4 (23rd December 2016) - von Harbou, Erik; Behrens, Richard; Berje, Jürgen; Brächer, Alexander; Hasse, Hans
Abstract: A liquid thermostated microreactor Nuclear Magnetic Resonance (NMR) probe head is presented that facilitates the investigation of kinetics of fast reactions. With this setup, reaction kinetics can be studied in a broad temperature (–20 – 100 °C) and pressure range (0 – 60 bar). The setup and NMR probe head are discussed from a reaction engineering standpoint based on experiments and simulations. The microreactor probe head widens significantly the range of applications of online NMR spectroscopy for reaction and process monitoring. Abstract : A liquid thermostated microreactor Nuclear Magnetic Resonance (NMR) probe head is presented that facilitates the investigation of fast reactions. The NMR probe head is discussed from a reaction engineering standpoint based on experiments and simulations. The NMR probe head widens significantly the range of applications of online NMR spectroscopy.